Destination Choice and Land Use in the Øresund region - A Modelling approach - Persson, Christer (Proceedings from the Annual Transport Conference at Aalborg University, 1998)
The Øresund Traffic Model is designed to forecast the future amount of traffic on the Fixed Link between Copenhagen and Malmö, it is developed for Øresundskonsortiet by COMVIN J/V. This paper gives an overview of the short distance model, which is one of several sub-models in the Øresund Traffic Model. The short distance model has trips made in the region defined by Skåne and the Hovedstad region as its scope. It is an destination/mode/route choice model. As an option, it can be used as a land use model. Economic and cultural barrier effects for trips between Denmark and Sweden are explicitly incorporated in the model